CRISPR-Cas technology, the tool of the future - Esquivel Álvarez, Alejandro (2022)
The CRISPR-Cas system discovered in the eighties consists of a series of RNA proteins that signal and messengers of the immune system in prokaryotic organisms to protect against invading antigens of various sources. After the CRISPR-Cas discovery, many research advances were made in the following decades regarding knowledge, techniques, and applications. This showed the system could edit the DNA in an exact and specific manner, which made it very promising to exploit it in various fields, such as the therapeutic field. New therapies of various diseases, industrial applications, food manufacturing, among others, make its impact quite relevant. The following review will focus on the fundamental understanding and implications of CRISPR-Cas techniques has with an ethical and legal view. In addition, to explore some of the applications present and future in the healthcare department, some methods of drug delivery in gene therapy, and new research that is being developed with the CRISPR-Cas technology.